2023
DOI: 10.1088/1572-9494/accb8d
|View full text |Cite
|
Sign up to set email alerts
|

Solving nonlinear soliton equations using improved physics-informed neural networks with adaptive mechanisms

Abstract: Partial differential equation (PDE) is an important tool for scientific research and are widely used in various fields. However, it is usually very difficult to obtain accurate analytical solutions of partial differential equations, and numerical methods to solve PDEs are often computationally intensive and very time-consuming. In recent years, Physics Informed Neural Networks (PINNs) have been successfully applied to find numerical solutions of partial differential equations (PDEs) and have shown great potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…[8,9] Another exciting area of advancement is the utilization of deep neural networks for solving various types of partial differential equations (PDEs) and modeling complex natural physical phenomena. [10][11][12][13] In this context, Raissi et al introduced the concept of physicsinformed neural networks (PINNs), which represents an improvement over traditional neural network-based methods for solving forward and inverse problems of partial differential equations. Numerous studies have shown that PINNs can effectively integrate the intrinsic constraint information in the physical equations.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Another exciting area of advancement is the utilization of deep neural networks for solving various types of partial differential equations (PDEs) and modeling complex natural physical phenomena. [10][11][12][13] In this context, Raissi et al introduced the concept of physicsinformed neural networks (PINNs), which represents an improvement over traditional neural network-based methods for solving forward and inverse problems of partial differential equations. Numerous studies have shown that PINNs can effectively integrate the intrinsic constraint information in the physical equations.…”
Section: Introductionmentioning
confidence: 99%